Global Image Through Local Cuisine: Exploring Culinary Diversity In Global Tourism - Julian Andriani Putri; Tuwuh Adhistyo Wijoyo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Over the past few decades, the global tourism industry has seen significant growth, leading to an increased demand for culturally immersive travel experiences. This study the importance of food in modern tourism, where it serves not only as a basic necessity but also as a vital tool for experiencing and understanding local cultures. Local cuisine, often referred to as